(Wo)men in Terrorism: From Chechnya's Black Widows to the Women in the Islamic State - Waddell-Harris, Mackenzie (Université d'Ottawa | University of Ottawa, 2017)
This research paper addresses a theme that is generally ignored in the political science and international relations literature – women in terrorism. Women are typically viewed as passive or coerced actors in terrorism rather than active perpetrators of violence. This perception hinders counter-terrorism policies and perpetuates gendered assumptions about women’s roles in terrorist groups. This research paper challenges traditional assumptions about women and violence; it explores the roles of women in modern terrorism through a case study of two groups: The Black Widows in Chechnya and the Islamic State of Iraq and Syria. The paper is structured as follows. Part One introduces the phenomenon of women in terrorism, and includes a discussion on the international issue of defining terrorism as well presents a theoretical framework on women, gender, and terrorism. Part Two applies a case study approach to assess women’s participation in the Black Widows and in the Islamic State to highlight many of the false assumptions about women’s roles in terrorist activities. Lastly, Part Three examines how women can be strategic partners in counter-terrorism practices and policies. A focus on women in terrorism can enhance knowledge and make a valuable contribution to the field of international relations.